The poison tree - Kelly, Erin, 1976- (Penguin Books, 2012)
Picking up Rex after a ten-year prison sentence for murder, Karen remembers the bohemian summer in 1990s London when their carefree romance and excesses became subject to a complicated family history and ended in violence.